2017
DOI: 10.1371/journal.pone.0168975
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Ebola Treatment Trials to Assess the Extent to Which They Adhere to Ethical Guidelines

Abstract: BackgroundObjective: To determine to what extent each trial met criteria specified in three research frameworks for ethical trial conduct.Design: Systematic review and narrative analysisMethods and findingsData sources: MEDBASE and EMBASE databases were searched using a specific search strategy. The Cochrane database for systematic reviews, the PROSPERO database and trial registries were examined. A grey literature search and citation search were also carried out.Eligibility criteria for selecting studies: Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Ethical issues also arose around equity in access to health care for participants and nonparticipants [44,50,59]. There were calls for international standards for the conduct of emergency research [21,51,60,62], [51], acceptable study designs [14] and simplified consent methods [2,3,6,25,37,46,51,70,74]. Some studies explored waivered consent [2,25,69,70,74] and/or proxy consent [69].…”
Section: Disseminationmentioning
confidence: 99%
“…Ethical issues also arose around equity in access to health care for participants and nonparticipants [44,50,59]. There were calls for international standards for the conduct of emergency research [21,51,60,62], [51], acceptable study designs [14] and simplified consent methods [2,3,6,25,37,46,51,70,74]. Some studies explored waivered consent [2,25,69,70,74] and/or proxy consent [69].…”
Section: Disseminationmentioning
confidence: 99%
“…A systematic review has reported on whether the Ebola clinical treatment trials in West Africa adhered to ethical guidelines [29]. The authors of the report excluded the experience in Sierra Leone because it appeared that "giving 100 consecutive patients atorvastatin and irbesartan constituted 'compassionate use' and did not require ethical approval" [29].…”
Section: The Ebola Treatment Experience Was Ethically Complicatedmentioning
confidence: 99%
“…A systematic review has reported on whether the Ebola clinical treatment trials in West Africa adhered to ethical guidelines [29]. The authors of the report excluded the experience in Sierra Leone because it appeared that "giving 100 consecutive patients atorvastatin and irbesartan constituted 'compassionate use' and did not require ethical approval" [29]. The authors of this review mistakenly assumed that all four authors of one of the two statin/ARB treatment reports (DSF, SMO, JRJ, and OMR; [8]) had known of plans to give the two drugs to Ebola patients, when in fact three of the authors (DSF, SMO, and JRJ) first learned that they had been given in late November 2014, several weeks after news first emerged that treatment appeared to have been successful.…”
Section: The Ebola Treatment Experience Was Ethically Complicatedmentioning
confidence: 99%
“…with promising results for certain antivirals [4][5][6] , passive immunotherapy and vaccinations 7,8 . On one hand, EBOV 14 infected nonhuman primates (NHPs) treated early with monoclonal antibodies (mAbs) were able to recover after 15 challenged with a lethal dose of EBOV 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Eq. (5). For simplicity, the mAbs are assumed to have a stable and long elimination half-life of 28 days across the 132 subjects 30 .…”
mentioning
confidence: 99%